Bounds in Cohen’s idempotent theorem - Sanders, T (Springer Verlag, 2020)
Suppose that G is a finite Abelian group and write W(G) for the set of cosets of subgroups of G. We show that if f:G→Z satisfies the estimate ∥f∥A(G)≤M with respect to the Fourier algebra norm, then there is some z:W(G)→Z such that